Proceedings of the 13th International Joint Conference on Biomedical Engineering Systems and Technologies 2020
DOI: 10.5220/0008945700830094
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining in Clinical Trial Text: Transformers for Classification and Question Answering Tasks

Abstract: This research on data extraction methods applies recent advances in natural language processing to evidence synthesis based on medical texts. Texts of interest include abstracts of clinical trials in English and in multilingual contexts. The main focus is on information characterized via the Population, Intervention, Comparator, and Outcome (PICO) framework, but data extraction is not limited to these fields. Recent neural network architectures based on transformers show capacities for transfer learning and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…39 In another example, the authors reported using Google Colab GPUs, along with estimates of computing time for different training settings. 68 3.4.2.4 Is the source code available?…”
Section: Is There a Description Of The Hardware Used?mentioning
confidence: 99%
See 2 more Smart Citations
“…39 In another example, the authors reported using Google Colab GPUs, along with estimates of computing time for different training settings. 68 3.4.2.4 Is the source code available?…”
Section: Is There a Description Of The Hardware Used?mentioning
confidence: 99%
“…A small number of publications did a real-life assessment, where the data extraction algorithm was applied to different, unlabelled, and often much larger datasets or tested while conducting actual systematic reviews. 30,33,39,42,68,71,72 3.4.3.2 Are basic metrics reported (true/false positives and negatives)?…”
Section: Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A sentence-based classifier can be used to label sentences as containing target information, and has been the method of extraction used in previous work Kiritchenko et al, 2010;Schmidt et al, 2020). But this does not fit in well with the desired tabular output for all target fields: the same information can appear in multiple sentences and the same sentence can contain multiple targets.…”
Section: Data Extractionmentioning
confidence: 99%
“…Kiritchenko et al (2010) create an extraction system that identifies sentences and then post-processes them to extract data, but operate only on structured HTML & XML. Schmidt et al (2020) apply fine-tuned BERT-based Transformers to the task of to sentence classification for semi-automated systematic review. Goswami et al (2019) build a PDF retrieval system for systematic reviews for psychology and use a random forest classifier to identify sentences for extraction.…”
Section: Related Workmentioning
confidence: 99%